Modeling and PID Control of a Quadrotor Aerial Robot - Ismail, Mohd Khairuddin; Anwar, P. P. A. Majeed; Abdul Aziz, Jaafar; Jessnor Arif, Mat Jizat (Trans Tech Publications, Switzerland, 2014)
This paper elucidates the modeling of a + quadrotor configuration aerial vehicle and the design of its attitude and altitude controllers. The aircraft model consists of four fixed pitch angle propeller, each driven by an electric DC motor. The hovering flight of the quadrotor is governed by the Newton-Euler formulation. The attitude and altitude controls of the aircraft were regulated using heuristically tuned (Proportional-Integral-Derivative) PID controller. It was numerically simulated via Simulink that a PID controller was sufficient to bring the aircraft to the required altitude whereas the attitude of the vehicle is adequately controlled by a PD controller.